Oviposition and feeding avoidance in Helicoverpa armigera (Hübner) against transgenic Bt cotton. (29th February 2016) - Zhao, D.; Zalucki, M. P.; Guo, R.; Fang, Z.; Shen, W.; Zhang, L.; Liu, B.
Abstract: Helicoverpa armigera (Hübner), the major target pest of transgenic Bacillus thuringiensis (Bt) cotton, remains susceptible to Bt cotton in China at present. Behavioural avoidance by ovipositing females might lead to reduced exposure to Bt cotton and minimize selection for physiological resistance. We examined the behavioural responses of H. armigera to Bt and non‐Bt cottons to determine whether behavioural avoidance to Bt cotton may be present. In oviposition choice tests, the number of eggs on non‐Bt cotton plants was significantly higher than on Bt cotton plants. Similarly, in no‐choice tests, Bt cotton plants attracted significantly fewer eggs compared with non‐Bt cotton plants. H. armigera neonates showed higher dispersal and lower establishment on Bt cotton than on non‐Bt cotton. First instars were found to feed consistently on non‐Bt cotton leaves, creating large feeding holes, but only produced tiny feeding holes on Bt cotton leaves. The H. armigera population used in this study showed avoidance of oviposition and feeding on Bt cotton. Our results provide important insights into one possible mechanism underlying the durability of Bt cotton resistance and may be useful for improving strategies to sustain the effectiveness of Bt crops.